Cardiac Effect of Aqueous Extract of Avicennia Marina on Isolated Rabbit's Heart - Ramesh Kumar Tanwani , Muhammad Jan , Muhammad Azhar Mugha! , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2011)
Objective: To find out the effect of Avicennia marina plant on the Isolated heart. Design: Experimental interventional study. Place & Duration: Study conducted at BMSI, JPMC, Karachi. Subjects & Methods: An aqueous extract obtained from the leaves of traditional medicinal plant Avicennia marina (Mangrove) tested on isolated heart of Rabbit, using the langendorff heart preparation. Administration of extract into the retrograde perfusion solution induced cardio-activity in Vitro. Results: Aqueous extract possessed positive inotropic and negative chronoscopic effect in langendorff method of heart preparation. Pre-treatment with atenolol and verapamil failed to antagonize / to modify the cardiac effect produce by aqueous extract. This showed that effect produced by extract is not mediated through beta adrenergic receptors or calcium channels. Conclusion: Mangrove plant extract showed increased in force and decreases in rate of contraction of isolated mammalian heart, which was most probably not mediated by beta adrenergic receptors or calcium channels.